New Chinese species of the genus Thalassaphorura Bagnall, 1949 (Collembola: Onychiuridae) - Sun, Xin; Li, Yu (Zootaxa, 2015)
Thalassaphorura is the most diverse genus in China so far. Three new species (T. guangdongensis sp. nov., T. xihuensis sp. nov. and T. linzhiensis sp. nov.) are reported from China. T. guangdongensis sp. nov. is characterized by its pso formulae (32/122/33343 dorsally and 11/000/01010 ventrally), 4+4 medial p-chaetae between posterior pso on head, 2+2 chaetae on Abd. I–III terga along axial line and axial chaeta m0 present on Abd. VI tergum. T. xihuensis sp. nov. belongs to the group of species characterized by the presence of only 4 papillae in AIIIO. T. linzhiensis sp. nov. is most similar to T. hainanica Sun, Gao & Potapov, 2014, and differs from the latter by undifferentiated S-chaetae, more vesicles in PAO, two axial chaetae on Abd. VI tergum, the presence of chaetae on Th. I sternum and longer anal spines.